Negative effects of nitrogen override positive effects of phosphorus on grassland legumes worldwide - Tognetti, Pedro Maximiliano (2021)
Fil: Tognetti, Pedro Maximiliano. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas Vinculadas a la Agricultura (IFEVA). Buenos Aires, Argentina.